1st European Congress of Medical Physics September 1–4, 2016; Medical Physics innovation and vision within Europe and beyond. (September 2017) - Tsapaki, Virginia; Kagadis, George C.; Brambilla, Marco; Ciocca, Mario; Clark, Catharine H.; Delis, Harry; Mettivier, Giovanni
Abstract: Medical Physics is the scientific healthcare profession concerned with the application of the concepts and methods of physics in medicine. The European Federation of Organisations for Medical Physics (EFOMP) acts as the umbrella organization for European Medical Physics societies. Due to the rapid advancements in related scientific fields, medical physicists must have continuous education through workshops, training courses, conferences, and congresses during their professional life. The latest developments related to this increasingly significant medical speciality were presented during the 1st European Congress of Medical Physics 2016, held in Athens, September 1–4, 2016, organized by EFOMP, hosted by the Hellenic Association of Medical Physicists (HAMP), and summarized in the current volume.